Vertical farming under protected cultivation for enhancing farmers’ income in Bundelkhand - Singh, R. K.; Singh, Akanksha; Singh, Saurabh; Dwivedi, S. V. (Indian Horticulture, 2025)
Vertical farming refers to the growing of crops, mostly vegetables and herbs on stacks of shelves indoors using artificial light and nutrient solutions, eliminating the need for sunshine and soil. It often incorporates controlled-environment agriculture, which rules out the adverse effects of climate change and focuses on optimizing plant growth conditions by employing soilless farming techniques. A comparison with the conventional/horizontal farming reveals the needs, constraints, implementation opportunities and possible alternative approaches, highlighting the potential of vertical farming technology as a viable option for food and nutritional security in India. This innovative approach involves indoor farming, leveraging cutting-edge technologies to create new paradigm in agriculture.